Decreasing incidence of pregnancy among HIV-positive adolescents in a large HIV treatment program in western Kenya between 2005 and 2017: a retrospective cohort study - Millar, Heather C. (Reprod Health, 2020)
BACKGROUND: The objective of this study was to estimate the prevalence, incidence and risk factors for pregnancy among HIV-positive adolescents in a large HIV treatment program in western Kenya. METHODS: The Academic Model Providing Access to Healthcare (AMPATH) program is a partnership between Moi University, Moi Teaching and Referral Hospital and a consortium of 11 North American academic institutions. AMPATH currently provides care to 85,000 HIV-positive individuals in western Kenya. Included in this analysis were adolescents aged 10–19 enrolled in AMPATH between January 2005 and February 2017. Socio-demographic, behavioural, and clinical data at baseline and time-updated antiretroviral treatment (ART) data were extracted from the electronic medical records and summarized using descriptive statistics. Follow up time was defined as time of inclusion in the cohort until the date of first pregnancy or age 20, loss to follow up, death, or administrative censoring. Adolescent pregnancy rates and associated risk factors were determined. RESULTS: There were 8565 adolescents eligible for analysis. Median age at enrolment in HIV care was 14.0 years. Only 17.7% had electricity at home and 14.4% had piped water, both indicators of a high level of poverty. 12.9% (1104) were pregnant at study inclusion. Of those not pregnant at enrolment, 5.6% (448) became pregnant at least once during follow-up. Another 1.0% (78) were pregnant at inclusion and became pregnant again during follow-up. The overall pregnancy incidence rate was 21.9 per 1000 woman years or 55.8 pregnancies per 1000 women. Between 2005 and 2017, pregnancy rates have decreased. Adolescents who became pregnant in follow-up were more likely to be older, to be married or living with a partner and to have at least one child already and less likely to be using family planning. CONCLUSIONS: A considerable number of these HIV-positive adolescents presented at enrolment into HIV care as pregnant and many became pregnant as adolescents during follow-up. Pregnancy rates remain high but have decreased from 2005 to 2017. Adolescent-focused sexual and reproductive health and ante/postnatal care programs may have the potential to improve maternal and neonatal outcomes as well as further decrease pregnancy rates in this high-risk group.